CORPORATE STORYTELLING FOR SUSTAINABILITY AND CLIMATE ACTION (SDG 13) (Lex localis - Journal of Local Self-Government, 2025)
Climate change could be considered one of the most urgent global issues which should be united in their efforts by governments, the civil society, and businesses. The first sustainable development goal (SDG 13: Climate Action) underlines the importance of the urgency in making impromptu measures in dealing with the problem of climate change and its impacts. Even though a substantial percentage of companies are adopting sustainability models and executing climate initiatives, the success or failure of these initiatives is often stipulated with regard to channels of conveying the message to the stakeholders. In this paper, the author describes potential effectiveness of corporate storytelling in terms of the sustainability communications, action on climate as effective strategy. The reviewed study observes that climate strategies have become humanized, as has the establishment of trust, and mobilizing and heating collective responsibility, emotional coming together: and all these powers of story- telling can be demonstrated by looking at other literature. Research has shown that corporate storytelling raises corporate legitimacy, as well as climate change being more bearable and feasible to SDG 13. However, the issue of greenwashing also emphasizes the need of transparency and responsibility of the narrative practices. The findings suggest that storytelling, when performed with honesty towards it, is a good action enabler on climate and is a necessary component of corporate sustainability reports.